PELATIHAN PENGOLAHAN BUAH NANAS PROGRAM KKNT DALAM MENDUKUNG MBKM GUNA MENINGKATKAN PELUANG BISNIS DESA TANJUNG BARU - Masawir, Bambang; Munandar, Aris; Kurniawan, Mohammad (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Located in Muara Enim Regency, Tanjung Baru Village in Lembak Sub-district has an abundance of natural resources, one of which is a pineapple plantation that deserves attention. Thanks to the village's dry soil consisting of sand and low lime content, pineapple cultivation thrives here. In fact, locals often turn to pineapple cultivation for their livelihood. Unfortunately, the sheer number of people owning these plantations has led to a surplus of pineapples, resulting in a drop in prices and lost opportunities for profit. As students, our goal is to foster MSMEs in Tanjung Baru Village through hands-on training on how to make delicious pineapple jam. We strive to provide locals with essential knowledge to effectively utilize pineapple products and delve into researching key ingredients that have the potential to cultivate and trade high-quality pineapples at the best prices. Our goal is to assist the development of MSMEs in Tanjung Baru Village.